Self-reported prenatal oral health-care practices of preterm low birth weight-delivered women belonging to different socioeconomic status: A postnatal survey - Gayathri Priyadarshni Elangovan; Jananni Muthu; Indra Kumar Periyasamy; Pratebha Balu; R Saravana Kumar (Wolters Kluwer Medknow Publications, 2017)
Background: The differences in the oral health status between the individuals with a high socioeconomic status (SES) and those with a low SES had markedly increased. There is, however, minimal information available on women understanding the need of dental hygiene for overall health and whether pregnant women comply with the current oral health strategies. In Lieu with the above, the present study aims to assess the awareness, dental hygiene practices, and the frequency of dental visits during pregnancy in postnatal women who delivered preterm low birth weight babies of different SES in and around Puducherry. Materials and Methods: A total of 200 individuals who visited Rajiv Gandhi Maternity Centre, Puducherry for delivery were selected. Information regarding onset of prenatal care, referral to dentist, and oral hygiene habits such as frequency of brushing, type of brush used, method of brushing, and frequency of brush change were obtained. Periodontal health status was recorded using PSR system. Results: Awareness of oral hygiene practices was more among upper middle class and lower middle class compared to upper lower strata. Visit to dentist during perinatal period was high among upper middle class compared to other socioeconomic strata. Conclusions: The awareness of oral health-care practices and importance of oral care during perinatal period were less among low socioeconomic strata.